Health implications of social networks for children living in public housing. (November 2015) - Kennedy-Hendricks, Alene; Schwartz, Heather L.; Griffin, Beth Ann; Burkhauser, Susan; Green, Harold D.; Kennedy, David P.; Pollack, Craig Evan
Abstract: This study sought to examine whether: (1) the health composition of the social networks of children living in subsidized housing within market rate developments (among higher-income neighbors) differs from the social network composition of children living in public housing developments (among lower-income neighbors); and (2) children's social network composition is associated with children's own health. We found no significant differences in the health characteristics of the social networks of children living in these different types of public housing. However, social network composition was significantly associated with several aspects of children's own health, suggesting the potential importance of social networks for the health of vulnerable populations. Highlights: This study examines the peer networks of children living in public housing. Female children with more unhappy friends had worse mental health. Social networks were associated with alcohol use among teens. Public housing location did not significantly impact social networks.